Participatory action research and co-researching as a tool for situating youth knowledge at the centre of research. (1st November 2019) - Martin, Staci; Burbach, Jessica; Benitez, Lulis Lares; Ramiz, Irisa
Too often youth from vulnerable communities see themselves talked about in academic research, but are rarely involved as co-researchers or co-authors of research. The purpose of this article is to share our reflections on engaging youth, their experiences and their perspectives on the multi-levels of impact of participatory action research methodologies, such as community-based action research or youth participatory action research. This article discusses more broadly how our participatory methodologies have impacted our co-researchers and ourselves. In it, we provide additional details about our past research projects, as well as theorizing those details in terms of how critical theory serves as a tool within participatory methodologies. We reflect on the experiences engaging participatory methodologies in two different contexts and examine the collective impacts, comparing and contrasting the findings. We draw on our field research: one researcher worked with co-researchers from Kakuma Refugee Camp, Kenya, and the other worked alongside youth co-researchers from an alternative secondary school in the USA. Two of our co-authors are also co-researchers, and they offer a deeper insight into how these methodologies impacted their lives.